The Economics and Econometrics of Gene–Environment Interplay - Biroli, Pietro; Galama, Titus; von Hinke, Stephanie; van Kippersluis, Hans; Rietveld, Cornelius A; Thom, Kevin (Review of Economic Studies, 2026)
Abstract We discuss how to estimate the interplay between genes (nature) and environments (nurture), with an empirical illustration of the moderating effect of school starting age on one’s genetic predisposition towards educational attainment. We argue that gene–environment (G×E) studies can be instrumental for (i) assessing treatment effect heterogeneity, (ii) testing theoretical predictions, and (iii) uncovering mechanisms, thereby improving understanding of how (policy) interventions affect population subgroups. Empirically, we find that being old-for-grade and having a higher genetic propensity for education benefits children on assessment tests as they progress through school. In this setting, families appear to increase genetic inequalities while schools seem to reduce them.